Biochemical assays and simple sequence repeat markers characterization of local and improved Nigerian cowpea [Vigna unguiculata (L.) Walp] varieties - Chika, Nwachukwu Emmanuel (2019)
Cowpea (Vigna unguiculata L. Walp) is an important food and fodder crop in the semi-arid tropics of Africa. In Nigeria, it serves as a principal source of energy, protein, vitamins and mineral nutrients for the people in the region. The aim of this study was to characterize cowpea accessions from Nigeria in order to generate information that could be used to design appropriate breeding and conservation strategies. In this study, five local cowpea varieties from local Abuja market and five improved varieties from International Institute of Tropical Agriculture (IITA) and National Centre for Genetic Resources and Biotechnology (NAGRAB), Nigeria, were screened to ascertain the genetic variation using biochemical analysis (antioxidant, anti-nutritional, mineral element and amino acid) and PCR-based molecular marker; Simple Sequence Repeats (SSR). In the first objective, the protein content was determined using Kjeldahl method, while spectrophotometer was used to measure the antioxidant (antioxidant activities, phenolics and flavonoids) and anti-nutritional values (phytate, alkaloid and tannin). The mineral analyses of (Calcium, Iron and Zinc) were carried out using Optimal Emission Spectroscopy 2000DV and the amino acid analysis was performed using High Performance Liquid Chromatography (HPLC). There were significant differences for Nutritional, Antioxidants, Anti-nutritional, Amino acids and Mineral content among 10 local and improved cowpea accessions from Nigeria. The seed protein content ranged from 22.61% to 27.92% indicating a significant variation among the cowpea genotypes. Highest protein content was recorded in improved variety NG/SA/0661 (27.92%) as compared to other varieties. The highest moisture contents were found in sweet honey (10.52%) and Sampea 10 (10.52%). Big white (4.28%) showed the highest seed ash content. There was a slight variation in the antioxidant properties ranging from (1.70-3.42mg/TAE/g) in phenolic and (1.67- 2.31mg/QE/g) in flavonoids. The highest total phenolic content (TPC) recorded among local and improved varieties was in the genotypes Big brown (3.43mg/TAE/0.1g) and Sampea 10 (3.132mg/TAE/0.1g). The results obtained showed the highest total flavonoid contents was found in the Butter beans (2.2QE/g) and NG/AO/035 (2.31QE/g) varieties. The anti-nutritional results clearly showed that cowpea seeds contain more tannin (1.92-5.72mg/g) than phytate (0.84-1.94mg/g) and alkaloid (0.24-2.54mg/g). The highest Phytate content was found in Big white (1.94mg/g) and NG/SA/0661 (1.89mg/g). The highest alkaloid was noted in Big white variety at (2.54mg/g) and the highest tannin was recorded in Small white (5.72mg/g). The total amino acid ranged from 13.43g/100g-16.20g/100g. The highest total amino acid was recorded in NG/AO/035 ((16.20g/100g) and Sampea 9 (15.77g/100g). NG/SA/0661 proved the highest total essential amino acid (48.21%), highest total basic amino acid (19.39%), and highest total neutral amino acid (54.17%). The highest total non-essential amino acid and the highest total acid amino acid was recorded in Sampea 11 at (57.85%) and (32.05%) respectively. The mineral element content varied from (45.61±1.22mg/g-14.79±0.24mg/g) in Ca, (2.29±0.06-0.94±0.02mg/g) in Fe and (2.1±0.02-0.96±0.02mg/g) in Zn. The highest calcium content was found in the genotype Big brown (45.61mg/g) and Big white (2.29mg/g) recorded the highest iron content. The highest zinc content was noted in Big white genotype at (2.1mg/g). In the last objective, a total five local and five improved varieties were genotyped using 19 SSR primers. A wide genetic variation was observed with the allele sizes ranging from 160 to 300bp. The average number of alleles was two per locus. The polymorphic information content (PIC) ranged from 0.32 to 0.59 (average of 0.46). The analysis of molecular variance showed percentages of molecular variance of 76% within population and 24% among population. The study established the existence of considerable genetic variation among Nigerian cowpea varieties. The genetic variation and relationships observed in this research provide insights for cowpea conservation and utilization in Nigeria. The variation in the protein and mineral content found among cowpea accessions could also be exploited for selection of cowpea improvement in Nigeria.